2019
DOI: 10.7717/peerj.8064
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic analysis of the PAL genes in five Rosaceae species and functional identification of Chinese white pear

Abstract: Phenylalanine ammonia lyase (PAL) plays an important role in the biosynthesis of secondary metabolites regulating plant growth response. To date, the evolutionary history of the PAL family in Rosaceae plants remains unclear. In this study, we identified 16 PAL homologous genes in five Rosaceae plants (Pyrus bretschneideri, Fragaria vesca, Prunus mume, Prunus persica, and Malus × domestica). We classified these PALs into three categories based on phylogenetic analysis, and all PALs were distributed on 13 chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 57 publications
5
23
0
Order By: Relevance
“…In the present study, there were two exons within most of the 14 PAL members (78.6% of cases). As can be seen from the clustering of Figure 3 b, StPAL proteins with similar exon/intron structures are more likely to cluster together, which is consistent with the results of PAL gene family analysis in most plants, such as maize [ 33 ], pear [ 34 ] and Juglans regia [ 35 ]. Among them, the intron/exon organization of StPAL7-StPAL14 is very similar.…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, there were two exons within most of the 14 PAL members (78.6% of cases). As can be seen from the clustering of Figure 3 b, StPAL proteins with similar exon/intron structures are more likely to cluster together, which is consistent with the results of PAL gene family analysis in most plants, such as maize [ 33 ], pear [ 34 ] and Juglans regia [ 35 ]. Among them, the intron/exon organization of StPAL7-StPAL14 is very similar.…”
Section: Discussionsupporting
confidence: 82%
“…PAL is one of the key enzymes during the synthesis of the well-known stress hormone, SA [ 22 ]. Elevated PAL activity or mRNA level was found in different plant species after exposure to various abiotic stresses [ 23 , 24 , 25 ]. The relative expression level of PAL was normalized with the two most stable reference genes and the least stable reference gene in oat according to the applied stress factor.…”
Section: Resultsmentioning
confidence: 99%
“…Wheat faces various types of biotic and abiotic stresses. It has been suggested that phenylalanine ammonia-lyase (PAL) genes are essential for plant growth, development, adaptation, and mitigation responses to various environmental and pathogens stresses by producing secondary metabolites regulating plant growth response [11,58,59]. Phenylpropanoids are plant-based organic compounds, which are produced from the amino acids phenylalanine and tyrosine.…”
Section: Discussionmentioning
confidence: 99%